Repetitive urine and blood sampling in neonatal and weaned piglets for pharmacokinetic and pharmacodynamic modelling in drug discovery: a pilot study. (October 2017) - Gasthuys, Elke; Schauvliege, Stijn; van Bergen, Thomas; Millecam, Joske; Cerasoli, Ilaria; Martens, Ann; Gasthuys, Frank; Vandecasteele, Tim; Cornillie, Pieter; Van den Broeck, Wim; Boyen, Filip; Croubels, Siska; et al.
Piglets are considered to be suitable animal models for predicting the pharmacokinetics and pharmacodynamics (PK/PD) of test drugs for potential use in the paediatric population. Such PK/PD studies require multiple blood and urine samplings. The goal of the present study was to determine a suitable blood collection strategy applicable in the youngest age categories of six days, four weeks and eight weeks of age, as well as a urine collection technique for male piglets in the same age categories. Blood was collected either by a surgically-placed jugular vein catheter (six days old [ n = 4] and four weeks old [ n = 2] piglets) or by direct venepuncture of the jugular vein (four weeks old [ n = 2] and eight weeks old [ n = 4] piglets). A non-invasive method for total volume urine collection in male piglets was also developed using a urine pouch. No specific complications were encountered during anaesthesia or surgery for jugular catheter placement. After a 24 h recovery period, urine and blood were easily collected without technical complications. One piglet was humanely killed at week 2 because of septicaemia. Histological analysis of both veins in all four piglets revealed negligible damage to the blood vessel wall. In conclusion, the presented techniques for blood (jugular catheter and direct venepuncture) and urine collection (pouches) are suitable for PK/PD studies in piglets.